The ideal graduate: fostering citizen participation through project-oriented problem-based learning - Alwi, Azlin (2018)
Many studies have found positive relationships between community engagement and students’ learning outcome. Students find relevance and are more connected to what they learn when they are exposed to real-life situation. Thus is it important to provide students with the ability to participate and engage in various civic initiatives to allow them the opportunity to develop themselves. However, the challenge is to include community engagement in the curriculum, specifically as part of a subject’s assessment. Also, in terms of teachers’ readiness, it requires teachers to shift their conventional teaching and learning methods towards a more engaging method. For students, they have to grow beyond traditional and passive role of problem solvers to become problem-definers. One teaching method that can address these issues is the project-oriented problem based learning (POPBL). Through project, students can be encouraged to participate in community building. The purpose of this study was to examine the effectiveness of POPBL in improving psychology student's perception of the course and citizenship participation. Seventy three undergraduate students participated in this study. As part of the project, students worked in a team of five to six members to identify one issue or problem affecting the community, and offered possible solution to the issue. Two measures were used (pre and post) to gauge students’ perception of their learning, and citizen participation. The results of paired samples t-tests show that the POPBL style improved students’ experience of teaching and learning, and participation in citizenship (specifically civic skills and civic participation.